The Ethnoscience of Oro Kino-Kino Traditional Play to Stimulate the Collaborative Skill and Learning Outcomes of Physics Learning - Albert Lumbu; I Ketut Mahardika; Supeno Supeno; Wachju Subchan (Universitas Lambung Mangkurat, 2024)
Ethnoscience-based knowledge helps produce new ways of managing the learning process. Ethnoscience is a bridge to explain knowledge in a society scientifically. This research aims to determine the ethnoscience of the traditional game Oro Kino-kino to stimulate collaboration skills and learning outcomes in physics learning. This research is a literature review and field observation. The data collection technique for this literature study is to use a database search tool to search for literature sources and field observations of the traditional game, oro kino-kino, starting from the terms of the game, number of players, rules, and steps. Ethnoscience of traditional games has been carried out by researchers in the principles of physics and the form of physics concepts in learning physics in everyday life. Integrating ethnoscience into physics learning is very important because it significantly impacts efforts to increase learning motivation, interest in learning, cooperation, and student learning outcomes. Ethnoscience in traditional games is very suitable for and familiar to students. The traditional game Oro Kino-kino in physics learning has the potential to make a positive contribution to increasing student motivation. The traditional game Oro Kino-kino in physics learning is related to the material of dynamics and equilibrium of rigid bodies because it can stimulate collaboration skills.